2013
DOI: 10.1007/s00134-013-2966-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensive care environment on family and patient satisfaction: a before–after study

Abstract: This is the first study to quantify the effect of ICU environment on family and patient satisfaction. Family and patient satisfaction with ICU experience increased by 6 % in the new ICU environment with noise-reduced, single rooms with daylight, adapted colouring and improved family facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 42 publications
1
96
0
3
Order By: Relevance
“…Of the 21 studies, 16 were based on single publications from a single cohort 17,[38][39][40][41][42][55][56][57][72][73][74][75][78][79][80] and five were based on multiple publications from overlapping cohorts. 9,10,53,54,[59][60][61][62][63][64][65][66][67][68][69][70][71]76,77 These studies are reported between 2002 and 2014.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 21 studies, 16 were based on single publications from a single cohort 17,[38][39][40][41][42][55][56][57][72][73][74][75][78][79][80] and five were based on multiple publications from overlapping cohorts. 9,10,53,54,[59][60][61][62][63][64][65][66][67][68][69][70][71]76,77 These studies are reported between 2002 and 2014.…”
Section: Settingmentioning
confidence: 99%
“…Most of the studies were based in North America -the USA (n = 9) 53,54,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][76][77][78][79][80] and Canada (n = 3) 9,10,56,74 -with other studies based in Greece (n = 2), 41,42 Switzerland (n = 2), 17,55 Germany (n = 1), 39 Israel (n = 1), 57 the Netherlands (n = 1), 75 the Philippines (n = 1) 38 and Turkey (n = 1). 40 Nine studies were single centre, with the remainder being multicentre, ranging from 2 to 23 centres.…”
Section: Settingmentioning
confidence: 99%
“…In this issue of ICM, Irene Jongerden and her colleagues [1] present the results of a before-and-after study that explores the effect of a change in ICU environment on family and patient satisfaction. Family satisfaction was measured by the FS-ICU [2][3][4], a much used and previously validated tool, while patient satisfaction was elicited by using an adapted version of this questionnaire.…”
mentioning
confidence: 99%
“…Because salient terms reflect factors important in shaping perceptions and experiences related to the ICU, these findings identify themes most likely to be associated with the satisfaction of patients and patients' family members with the ICU experience and care. [33][34][35][36][37] These themes can be used as a starting point for future studies to further refine the meaning of the themes to patients and patients' family members and ways to measure the themes.…”
Section: Discussionmentioning
confidence: 99%